Pharmacoeconomic Evaluation in Generalized Anxiety Disorder: A North India Perspective - Poddar, Rishi Kapoor; Mittal, Piyush (Journal of Neonatal Surgery, 2025)
Background: The most prevalent mental disorder is anxiety disorders. A common type of anxiety disorder is generalised anxiety disorder (GAD). Objectives of the study were to evaluate cost of illness (COI) and cost effectiveness of different pharmacological treatments in patients with GAD. Methods: This was a single centred prospective observational study. The duration of the study was one year. The inclusion criteria were patients with GAD, both male and female patients, patients within 18-60 years age group, and willingness to participate. Results: A total of 352 patients were analysed in the study. Escitalopram, venlafaxine XR and paroxetine were the drugs used as the treatment option for GAD patients. Quality-Adjusted Life Year (QALY) gained for paroxetine was found to be highest, followed by venlafaxine XR and escitalopram. Cost effectiveness of escitalopram, venlafaxine XR and paroxetine for GAD were found to be 3395, 4655, and 8554 ₹/QALY gained respectively. The COI attributable to GAD for six months was estimated ₹29945. Indirect costs constituted 70% of total costs whereas pharmacotherapy accounted for 22.5% of the COI. The contribution of absenteeism cost was 45.2% of the COI. Conclusion: Escitalopram is found to be cost effective compared with venlafaxine XR and paroxetine for the treatment of GAD. GAD shows significant economic burden as COI was significant around thirty thousand Indian rupees.